2023
DOI: 10.1021/acs.joc.3c01725
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylative Transformations Using a DMAP-Based Pd-Catalyst through Ex Situ CO Generation

Pallabi Halder,
Ashif Iqubal,
Krishanu Mondal
et al.

Abstract: A phosphine-free, efficient protocol for aminocarbonylation and carbonylative Suzuki–Miyaura coupling has been developed using a novel palladium complex, [PdII(DMAP)2(OAc)2]. The complex was successfully synthesized using a stoichiometric reaction between PdII(OAc)2 and DMAP in acetone at room temperature and characterized using single-crystal X-ray analysis. Only 5 mol % catalyst loading was sufficient for effective carbonylative transformations. “Chloroform-COware” chemistry was utilized for safe and facile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 97 publications
0
0
0
Order By: Relevance
“…We selected trifluoroacetimidoyl chloride 1a with n -butyl amine 2b as a model substrate to initiate the reaction (Table 1). The reaction was performed in the presence of the Pd/AFCs (1 mol%), PPh 3 (5 mol%) and K 2 CO 3 (2.0 equiv) in 1,4-dioxane at 100 °C for 12 h with benzene-1,3,5-triyl triformate (TFBen) as a convenient CO surrogate, 55–57 and to our delight, the desired 2-trifluoromethyl-quinazolin-4(3 H )-one product 3b was obtained in 76% yield (Table 1, entry 1). Prompted by the positive result, we next screened a series of organic solvents, which indicated that various commonly used solvents could serve as the reaction medium but the efficiency was inferior to that of 1,4-dioxane (Table 1, entries 2–6).…”
Section: Resultsmentioning
confidence: 99%
“…We selected trifluoroacetimidoyl chloride 1a with n -butyl amine 2b as a model substrate to initiate the reaction (Table 1). The reaction was performed in the presence of the Pd/AFCs (1 mol%), PPh 3 (5 mol%) and K 2 CO 3 (2.0 equiv) in 1,4-dioxane at 100 °C for 12 h with benzene-1,3,5-triyl triformate (TFBen) as a convenient CO surrogate, 55–57 and to our delight, the desired 2-trifluoromethyl-quinazolin-4(3 H )-one product 3b was obtained in 76% yield (Table 1, entry 1). Prompted by the positive result, we next screened a series of organic solvents, which indicated that various commonly used solvents could serve as the reaction medium but the efficiency was inferior to that of 1,4-dioxane (Table 1, entries 2–6).…”
Section: Resultsmentioning
confidence: 99%
“…A plausible reaction mechanism has been proposed based on the previous literature , and the observed results (Scheme ). Initially, the oxidative addition of the iodo-derivative 1 to Pd(0)­L 2 forms an arylpalladium species I .…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, the two-chamber reactor (COware) has emerged as a valuable tool for the safe handling of gaseous reagents . Addressing the challenges posed by one-pot chloroform-enabled carbonylative transformations, we have recently introduced the “Chloroform-COware ″ chemistry . This methodology provides a safe setting for carbonylation reactions, facilitating the smooth release of CO gas from chloroform in one chamber and the occurrence of carbonylative transformations under milder conditions in another chamber.…”
Section: Introductionmentioning
confidence: 99%
“…This catalyst proved to provide the best yield with a 97% NMR yield (90% of isolated yield of the product). Considering the disadvantages of using phosphine ligands, such as air and moisture sensitivity, high cost, and difficult purification from the final product, 21 and regarding some previous reports on phosphine-free aminocarbonylations, 22 we decided to investigate the reaction with the phosphine-free conditions afforded by the Pd-PEPPSI catalyst. When the reaction was performed in the absence of the Pd-PEPPSI catalyst, the formation of the aminocarbonylation product was not observed, as shown in Table 1 , entry 11.…”
Section: Results and Discussionmentioning
confidence: 99%